China as an international creditor - Juuso Kaaresvirta; Helinä Laakkonen (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2021)
China became the world's largest lender to emerging and developing economies over the past decade. At the same time, concerns on the debt sustainability of many of these countries have grown. Some countries have found themselves struggling to repay their loans and China has had to renegotiate debt restructurings bilaterally. As covid-19 pandemic hit many of the borrowers hard in 2020, China committed with all other G20 countries to the Debt Service Suspension Initiative (DSSI) to temporarily suspend official bilateral debt payment of 73 beneficiary countries. While China's overseas lending remain opaque, there is little evidence that China intentionally practices "debt-trap diplomacy."
urn:nbn:fi:bof-202103241168
Keywords: 330; China; loans; loan restructuring; low-income and emerging economies